ICT and Education: Evidence from Student Home Addresses - Felix Weinhardt; Benjamin Faber; Rosa Sanchis-Guarner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Governments around the world are making it a priority to upgrade information and communication technologies (ICT) with the aim to increase available internet connection speeds. This paper proposes a new empirical methodology to estimate the causal effect of these policies, and applies it to the question of how upgrades in ICT affect educational attainment. We draw on a new and unique collection of UK microdata that allows us for the first time to link administrative test score records for the population of English primary and secondary school students to the available ICT at their home addresses. To base estimations on exogenous variation in ICT, we notice that capacity constraints at telephone exchange stations lead to invisible and essentially randomly placed boundaries of station-level catchment areas that give rise to substantial and discontinuous jumps in the available ICT across space. Using this design across more than 20 thousand boundary segments in England, we find that even very large changes in available internet connection speeds have a precisely estimated zero effect on educational attainment, and that the estimates are causally identified: house prices, student socioeconomic characteristics and local amenities are flat across the boundaries. Guided by a simple theoretical framework we then bring to bear additional microdata on student time use and internet use to quantify the microeconomic channels underlying the zero reduced form effect. We find that faster connection speeds lead to a significant increase in student consumption of online content, but do not affect the amount of time spent online or the amount of time spent studying. We conclude that the elasticity of student demand for online content with respect to its per unit time cost is negative but bounded at -1, and that increased consumption of online content has no effect on learning productivity per unit of time spent studying.
Keywords: I21; D83; F15; 330